2000
DOI: 10.1152/ajpendo.2000.278.6.e985
|View full text |Cite
|
Sign up to set email alerts
|

Ability of insulin to modulate hepatic glucose production in aging rats is impaired by fat accumulation

Abstract: Increased total fat mass (FM) and visceral fat (VF) may account in part for age-associated decrease in hepatic insulin action. This study determined whether preventing the changes in body fat distribution abolished this defect throughout aging. We studied the F(1) hybrid of Brown Norway-Fischer 344 rats (n = 29), which we assigned to caloric restriction (CR) or fed ad libitum (AL). CR (55% of the calories consumed by AL) was initiated and used at 2 mo to prevent age-dependent increases in FM and VF. AL rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 31 publications
9
38
0
Order By: Relevance
“…Aged F344/BN rats are associated with insulin resistance and glucose intolerance, as shown in several previous reports [15,18,44]. In the present study, we also observed impaired glucose tolerance, as indicated by the elevated blood glucose levels after glucose loading in the aged obese F344/BN rats.…”
Section: Discussionsupporting
confidence: 91%
“…Aged F344/BN rats are associated with insulin resistance and glucose intolerance, as shown in several previous reports [15,18,44]. In the present study, we also observed impaired glucose tolerance, as indicated by the elevated blood glucose levels after glucose loading in the aged obese F344/BN rats.…”
Section: Discussionsupporting
confidence: 91%
“…We have found significant increases in this parameter in both young and aged animals, although it was more evident in aged animals; therefore, aging impairs insulin clearance (Table 1). Taking these results together, in agreement with other authors (Barzilai and Rossetti 1996), hepatic insulin resistance is suggested because it causes a decrease in the ability of insulin to modulate glycogen stores during aging (Gupta et al 2000). In this case, estradiol (AE) and high dose of genistein (AG2) also appeared to improve the insulin clearance Groups C and G2 of young rats spent significantly more time searching in the target quadrant (black bars).…”
Section: G1 Vs Eg2supporting
confidence: 90%
“…At the present time, we do not have a plausible explanation for these results. Likewise, it has been previously demonstrated that the increase in fasting serum insulin is due to impaired suppression of hepatic glucose production, which requires significant portal hyperinsulinemia (Gupta et al 2000).…”
Section: G1 Vs Eg2mentioning
confidence: 99%
“…Aging process is also associated with reduced compensatory beta cell mass function of the pancreas and to insulin resistance (Maneilly and Elliott, 1999) as well as with decreased mitochondrial function that contributes to insulin resistance (Petersen et al, 2003). A study by Gupta et al (2000) showed that hepatic insulin resistant was related to body fat and its distribution, and hepatic insulin action could be preserved by caloric restriction in aging caloric restriction rat.…”
Section: Age Insulin Resistance and Metabolic Syndromementioning
confidence: 99%